139 Wettemann Graduate Scholar in Physiology: Maternal nutrition alters concentrations of nutrients in fetal fluids and expression of genes impacting production efficiencies in bovine fetal liver, muscle, and cerebrum during the first 50. (7th December 2018) - Crouse, M; Caton, J; Cushman, R; Greseth, N; McLean, K; Reynolds, L; Dahlen, C; Borowicz, P; Ward, A
Abstract: We hypothesized that a moderate maternal nutrient restriction during the first 50 d of gestation in beef heifers would alter nutrient concentrations in fetal fluids, and affect transcript abundance of genes impacting production efficiency phenotypes in fetal liver, muscle, and cerebrum. Angus-cross heifers (n = 49) were synchronized, bred via AI, assigned to nutritional treatment (CON=100% of requirements for 0.45 kg/d gain and RES=60% of CON) and ovariohysterectomized on d 16, 34, or 50 of gestation (n=6 to 9/d); non-bred controls were ovariohysterectomized on d 16 of the estrous cycle (n=6). Histotroph, allantoic, and amniotic fluids were obtained from the uterine horn containing the conceptus. Fetal liver, muscle from the hind limb, and cerebrum were collected for RNA-seq on d 50 of gestation only (n=7/treatment). RNA-seq was conducted on the Illumina HiSeq 2500 platform using 50-bp paired-end reads at a depth of 2 × 10.4M reads/sample. Transcriptome analysis was performed using the Tuxedo Suite, and ontological analysis with DAVID 6.8. Differentially expressed genes were screened into categories associated with known impacts on production efficiencies. In all fluids, concentrations of hexoses and amino acids were influenced by day of gestation and maternal nutrition. Most notably, physiological fuels such as glucose were greater in CON compared with RES heifers in allantoic and amniotic fluids while glutamine was greater in RES compared with CON heifers on d 34 of gestation in amniotic fluid. The concentration of the methyl donor, methionine was greater in CON heifers in allantoic fluid. For fetal liver, muscle, and cerebrum, a total of 548, 317, and 151 genes, respectively (P<0.01) were differentially expressed, of which 201, 144, and 28 genes, respectively were false discovery rate protected (q<0.10). In fetal liver, 3 categories of interest were affected by nutritional treatment: metabolic pathways, protein kinase, and nucleosome core. In fetal muscle, 3 categories of interest were affected by nutritional treatment: skeletal muscle, embryogenesis, and signaling cascades. In fetal cerebrum, 2 categories of interest were affected by nutritional treatment: hippocampus and neurogenesis, and metal-binding. These results demonstrate that a moderate maternal nutrient restriction during the first 50 d of gestation in beef heifers alters the concentration of physiological fuels and methyl donors, as well as the transcript abundance of genes potentially impacting production efficiencies in fetal liver, muscle, and cerebrum. These data lay the foundation upon which further research identifying the phenotypic responses to changes in these pathways may be elucidated. USDA is an equal opportunity provider and employer.